Evaluating NO.sub.x emissions and their effect on O.sub.3 production in Texas using TROPOMI NO.sub.2 and HCHO - Goldberg, Daniel L; Harkey, Monica; de Foy, Benjamin; Judd, Laura; Johnson, Jeremiah; Yarwood, Greg; Holloway, Tracey (Atmospheric chemistry and physics, 2022)
The Tropospheric Monitoring Instrument (TROPOMI) on the Sentinel-5 Precursor (S5P) satellite is a valuable source of information to monitor the NO.sub.x emissions that adversely affect air quality. We conduct a series of experiments using a 4x4 km.sup.2 Comprehensive Air Quality Model with Extensions (CAMx) simulation during April-September 2019 in eastern Texas to evaluate the multiple challenges that arise from reconciling the NO.sub.x emissions in model simulations with TROPOMI. We find an increase in NO.sub.2 (+17 % in urban areas) when transitioning from the TROPOMI NO.sub.2 version 1.3 algorithm to the version 2.3.1 algorithm in eastern Texas, with the greatest difference (+25 %) in the city centers and smaller differences (+5 %) in less polluted areas. We find that lightning NO.sub.x emissions in the model simulation contribute up to 24 % of the column NO.sub.2 in the areas over the Gulf of Mexico and 8% in Texas urban areas. NO.sub.x emissions inventories, when using locally resolved inputs, agree with NO.sub.x emissions derived from TROPOMI NO.sub.2 version 2.3.1 to within 20 % in most circumstances, with a small NO.sub.x underestimate in Dallas-Fort Worth (-13 %) and Houston (-20 %). In the vicinity of large power plant plumes (e.g., Martin Lake and Limestone) we find larger disagreements, i.e., the satellite NO.sub.2 is consistently smaller by 40 %-60 % than the modeled NO.sub.2, which incorporates measured stack emissions. We find that TROPOMI is having difficulty distinguishing NO.sub.2 attributed to power plants from the background NO.sub.2 concentrations in Texas - an area with atmospheric conditions that cause short NO.sub.2 lifetimes. Second, the NOx/NO2 ratio in the model may be underestimated due to the 4 km grid cell size. To understand ozone formation regimes in the area, we combine NO.sub.2 column information with formaldehyde (HCHO) column information. We find modest low biases in the model relative to TROPOMI HCHO, with -9 % underestimate in eastern Texas and -21 % in areas of central Texas with lower biogenic volatile organic compound (VOC) emissions. Ozone formation regimes at the time of the early afternoon overpass are NO.sub.x limited almost everywhere in the domain, except along the Houston Ship Channel, near the Dallas/Fort Worth International airport, and in the presence of undiluted power plant plumes. There are likely NO.sub.x -saturated ozone formation conditions in the early morning hours that TROPOMI cannot observe and would be well-suited for analysis with NO.sub.2 and HCHO from the upcoming TEMPO (Tropospheric Emissions: Monitoring Pollution) mission. This study highlights that TROPOMI measurements offer a valuable means to validate emissions inventories and ozone formation regimes, with important limitations.